Electrical characterization of the polyaniline including boron/p-type silicon structure for optical sensor applications - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz (Elsevier Science Sa, 2008)
The charge transport properties of polyaniline including boron (PANI-B)/p-type silicon diode have been investigated. The current-voltage characteristics of the device have been investigated under white and ultraviolet light illuminations. Electronic parameters such as the barrier height. diode ideality factor and series resistance, were determined from the current-voltage (I-V) characteristics in the dark of the device and were found to be 0.81 eV, 3.58 and 1.67 x 10(6) Omega. respectively. The photocurrent for the device was found to be 0.857 mu A. The open circuit voltage (V-proportional to = 119.6 mV) under UV illumination is higher than that of the open circuit voltage under (V-proportional to = 57.6 mV) white light illumination, although the intensity of the UV light has lower value. The obtained photovoltaic results suggest that the polyaniline including boron/p-type silicon device can be used as a sensor in optical applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Diode; Organic layer; Photovoltaic properties